Perceived Barriers to Weight loss Programs for Overweight or Obese Women - Sharifi, Nasrin (Tabriz University of Medical Sciences, 2013)
Background: In order to develop appropriate obesity control and treatment strategies, the key point is to understand the barriers perceived by overweight or obese people in trying to follow weight-loss programs. This study examined perceived barriers to weight-loss programs among overweight or obese women. Methods: In this descriptive-analytical study, 204 overweight or obese women aged 31.97± 10.62 yr, were selected randomly from the nutritional counseling centers in 2008 in Tabriz, Iran. The mean BMI was 33.83 ±5.75 kg/ m2. A structured questionnaire including questions on barriers to weight-loss diet and physical activity was filled out for each participant by face-to-face interview. Height and weight measured objectively and demographic details were obtained. Data analysis carried out using multiple regression and factor analysis. Results: The most important perceived barriers to weight-loss diets were 'situational barriers', stress, depression, and food craving. High educational level was independent determinant of situational barriers (β=0.329, P=0.048). Employee women had a higher mean score on stress and depression than students and housewives. Lack of time and exercising lonely were the most important items of "External barriers" and Lack of motivation was the most important item of "internal barriers" to physical activity. Employment and being student were highly associated with external barriers (β=1.018, P<0.001 and β=0.541, P= 0.002). Moreover, older women who had low educational level, perceived more internal barriers. Conclusion: Weight reducing strategies should take into account the specific perceived barriers to weight-loss diets faced by overweight or obese women, particularly situational barriers, stress and depression and food craving; and lack of time and lack of motivation as barriers to physical activity.